Is Rotoscope True Animation? - Christine Mersiana Lukmanto (ULTIMART Jurnal Komunikasi Visual, 2017)
Throughout the years, technologies have developed varied techniques for animators to create films. One of the oldest and interesting techniques of animating is Rotoscope by tracing every single frame from live action footages and enhancing it with animator’s style. In terms of anthropomorphism, it creates an uncanny realistic effect because it mimics the reality of the structure, the proportion and the movement. Due to its easy process in animating, there are some critiques and debates about how far rotoscoping can be considered as the “true” animation. This research would cover the identity of rotoscoping, professionals and animator’s perspective as well as the aesthetic of this technique. Keywords: rotoscope, realism, true animation, perspective and aesthetic